DIVERSITY AND POTENTIAL UTILIZATION OF SOME WILD MACROSCOPIC FUNGI AROUND IPB UNIVERSITY CAMPUS BUILDING - Putra, Ivan Permana (Universitas Tanjungpura, 2020)
Mushroom are cosmopolitan organisms which can emerge in a variety of environment, and around the university building is no exception.The goal of this study was to collect information on macrofungi diversity around IPB Unversity Campus Building in order to be used as a reference for its potential in the future. Macrofungi collection was done by opportunistic sampling method. All mushrooms found were Basidiomycota, which dominated by order of Agaricales. A total of 13 mushrooms were identified and described in this study, namely: Armillariella sp., Marasmiellus sp., Mycena sp., Agrocybe sp., Polyporus sp., Entoloma sp., Xeromphalina sp., Paxillus sp., Lentinus sp. 1, Lentinus sp. 2, Collybia sp., Pluteus sp., and Parasola sp. Some macroscopic fungi found to be potentially used as a bioactive compound sources, medicine and also played an important role as a decomposer in the sampling site.AbstrakJamur makroskopis merupakan organisme kosmopolitan yang mampu tumbuh pada berbagai macam kondisi lingkungan, tidak terkecuali di sekitar bangunan universitas. Tujuan dari penelitian ini adalah menyediakan informasi mengenai keragaman jamur makroskopis di sekitar kampus Institut Pertanian Bogor untuk pemanfaatannya di masa mendatang. Eksplorasi jamur dilakukan dengan metode pengambilan sampel oportunistik. Semua jamur yang ditemukan merupakan filum Basidiomycota dan didominasi oleh ordo Agaricales. Sebanyak 13 jenis jamur makro berhasil diidentifikasi dan dideskripsikan pada penelitian ini, yaitu: Armillariella sp., Marasmiellus sp., Mycena sp., Agrocybe sp., Polyporus sp., Entoloma sp., Xeromphalina sp., Paxillus sp., Lentinus sp. 1, Lentinus sp. 2, Collybia sp., Pluteus sp., dan Parasola sp. Beberapa Jamur diketahui berpotensi sebagai sumber bahan bioaktif, obat-obatan, dan dekomposer penting pada ekosistem.Kata Kunci: Gedung kampus, Jamur, Ragam, Potensi, IPB